2007
DOI: 10.2337/dc06-1966
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing Improves Weight Loss in Women With Type 2 Diabetes

Abstract: OBJECTIVE -We sought to determine whether adding motivational interviewing to a behavioral weight control program improves weight loss outcomes and glycemic control for overweight women with type 2 diabetes.RESEARCH DESIGN AND METHODS -We conducted a randomized, controlled, clinical trial in which participants all received an 18-month, group-based behavioral obesity treatment and were randomized to individual sessions of motivational interviewing or attention control (total of five sessions) as an adjunct to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
295
7
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(315 citation statements)
references
References 44 publications
10
295
7
3
Order By: Relevance
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…34 MI has been shown to improve patients' general health status or well-being, promote physical activity, help develop healthier nutritional habits, and manage chronic conditions such as mental illness, hypertension, hypercholesterolemia, obesity, and diabetes. [37][38][39][40][41] Randomized controlled trials have shown that brief MI training for clinicians is effective for improving patient medication adherence, especially if there is follow-up contact after an initial training, 42,43 and even at low doses (i.e., two or three sessions). MI is effective as a pretreatment adjunct and as an approach for less motivated or prepared patients, and may be applied for a wide range of medications across diverse populations.…”
Section: Motivational Interviewing and Counselingmentioning
confidence: 99%
“…However, subjects in the control condition also lost weight that it is not surprising because they were also provided by standard nutritional education. In the study by West et al, subjects in both control and MI groups lost weight significantly, while females in MI group had lost notably more weight than the control subjects and MI had resulted in more stable outcomes compared to the standard program (39). In the study by Saffari et al, using MI technique, presented more efficacy in MI group than the control on reduction of BMI, weight, total fat and increased consumption of fruits and vegetables (40).…”
Section: Effectiveness Of MI Compared To That Of Standard Education Imentioning
confidence: 95%
“…Eighteen studies met the inclusion criteria out of thirty-five potential studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) . Seven of the studies recruited healthy obese participants, ten enrolled only participants with diabetes (18,19,21,23,26,30,31,(33)(34)(35) and one study recruited participants with hypertension (32) . Intervention duration ranged from 3?5 to 12 months (median of 6 months).…”
Section: Findings and Description Of Studiesmentioning
confidence: 99%
“…Incomplete outcome data were addressed in ten of eighteen trials. Six studies recruited only women participants (22,24,(26)(27)(28)(29) and the rest were of mixed gender. Most of the studies were clinic-or community-based, and only three were church-based (22)(23)(24) .…”
Section: Findings and Description Of Studiesmentioning
confidence: 99%